The Urgency of Forming Laws and Regulations on Citizen Lawsuits in Indonesia - Esfandiari, Fitria; Wahyu Pratama, Dimas; Anoraga, Surya; Wido Haruni, Catur (KnE Social Sciences, 2024)
This research aims to seek the formation of laws and regulations regarding Citizen Lawsuits. Citizen Lawsuitis access for citizens to represent the public interest to file lawsuits in court based on unlawful acts by the government. Since the receipt of the Citizen Lawsuit filed byMunir CS,based on the abandonment of TKI in Nunukan by the Government of Indonesia, until now there has been no regulationregarding Citizen Lawsuits. The formulation of the problem used in this study is first, what is the urgency of establishing legislation regarding Citizen Lawsuit in Indonesia, and second, what form of legislation regardingCitizen Lawsuit is ideally implemented in Indonesia. The research method used is normative-juridical research. The results of this study show that the condition of the legal vacuum regarding Citizen Lawsuit results in the inconsistency of the Panel of Judges in interpreting formal requirements, namely notifications; therefore, it is necessary to make laws and regulations regardingCitizen Lawsuits to catch up with written law and prevent inconsistencies in court decisions. In conclusion, the legal basis used by the Judges panel in accepting the Citizen Lawsuit was based on Article 10 Section (1) and Article 5 Section (1) of Law number 48 of 2009 concerning Judicial Power. Additionally, the Law of Civil Procedure should include the principle of Citizen Lawsuits, but since legislation takes time to pass, the Supreme Court can work around this by creating a PERMA. Suggestions from this research, it is necessary to make efforts to form regulations regarding Citizen Lawsuit, and it is necessary to research Citizen Lawsuit models in Anglo-Saxon countries to be used as reference material in formingCitizen Lawsuit regulations. Keywords: urgency, formation of legislation, citizen lawsuit